2022
DOI: 10.31234/osf.io/26j8w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changing the Incentive Structure of Social Media Platforms to Halt the Spread of Misinformation

Abstract: The powerful allure of social media platforms has been attributed to the human need for social rewards. Here we demonstrate that the spread of misinformation on such platforms is facilitated by existing social ‘carrots’ (e.g., ‘likes’) and ‘sticks’ (e.g., ‘dislikes’) that are dissociated from the veracity of the information shared. Testing 951 participants over six experiments, we show that a slight change to the incentive structure of social media platforms, such that social rewards and punishments are contin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Thus, interventions and social media design features should aim to both increase accuracy motivations and decrease motivations to share content that receives high social reward at the cost of accuracy. In line with this, experimental studies have found that providing social rewards for sharing high-quality content and punishments for sharing low-quality content 77 improves the quality of news people report intending to share. Additionally, making people publicly endorse that the news that they share is accurate 78 , or showing people that fellow in-group members believe content is misleading 79 , also improves people's sharing intentions.…”
Section: Discussionmentioning
confidence: 64%
“…Thus, interventions and social media design features should aim to both increase accuracy motivations and decrease motivations to share content that receives high social reward at the cost of accuracy. In line with this, experimental studies have found that providing social rewards for sharing high-quality content and punishments for sharing low-quality content 77 improves the quality of news people report intending to share. Additionally, making people publicly endorse that the news that they share is accurate 78 , or showing people that fellow in-group members believe content is misleading 79 , also improves people's sharing intentions.…”
Section: Discussionmentioning
confidence: 64%
“…Thus, social media companies should use people's expressed preferences for what they want to see on social media (e.g., positive, nuanced, educational, or entertaining content) as a proxy for interest, rather than ambiguous metrics such as attention or engagement. This could be achieved with modest changes to existing social media platforms (Globig et al, 2023;Pretus et al, 2023).…”
Section: Regulator and Agent Sophistication As An Explanation-generat...mentioning
confidence: 99%
“…When the incentive structure of social media changes, people adjust the type of content they share. For instance, when social media platforms reward the veracity or trustworthiness of a post, people are far more likely to share true information (Globig, Holtz, & Sharot, 2023;Pretus et al, 2023). Furthermore, this can be achieved with a relatively small tweak to the design features of a social media site.…”
Section: Regulator and Agent Sophistication As An Explanation-generat...mentioning
confidence: 99%